SPECIAL ASPECTS OF THE GRAIN HANDLING TERMINAL`S CONVEYOR GALLERY DESIGNING (Collection of scientific works «Modern structures of metal and wood», 2019)
One of the important tasks in the field of metal structures improving is to reduce their material consumption, which can be achieved by further studying the actual work of structures, improving  design  schemes,  developing  a  structural  form,  using  high-strength  steels,  and  using effective cross sections types of elements. In  the  article,  the  authors  investigate  the  question  of  rational  constructive  solutions  for the conveyor gallery of the grain handling terminal of the sea trade port. The length of designed conveyor gallery is 118.69 m and it consists of four spans (36, 18, 30, 30 m long) and five supports 5.86 m, 12.39 m, 15.65 m, 21.16 m, 26.68 m high, the gallery has a longitudinal  grade  of  12°.  Gallery  consists  of  the  one  temperature  unit.  At  the  same  time,  an existing  handling  station  is  adopted  by  a  fixed  support  providing  structural  stability  in  the longitudinal  direction,  the  remaining  supports  are  adopted  flat,  allowing  displacement  in  the longitudinal direction during temperature movements. A truss structure has been adopted among the various possible structural solutions  for the span structure, as the  most technologically  advanced and easy to install. Spans are carried out according to a discontinuous design and consist of two flat supporting trusses with a height of 3.2 m with parallel belts and a triangular lattice with additional posts  connected  to  each  other  in  a  three-dimensional  space  block  with  a  width  of  3.3  m  by transverse beams of covering and overlapping, horizontal ties along the lower and upper truss belts and supporting  frames  at the ends  having a rigid connection of the crossbar with the supporting posts  of  the  supporting  trusses.  The  loads  acting  on  the  gallery  –  erection  load,  technological, atmospheric, including episodic – seismic effects were found (the intensity of seismic impact was adopted 7 points, based on the data of the building area`s geotechnical conditions and in accordance with  the  class  of  responsibility  of  the  construction  object).  Calculation  of  steel  structures  of  the conveyor gallery was performed using the computer-aided engineering system SCAD. The sections of truss rods are designed with rectangular roll-welded slender hollow section, in accordance with the requirements of economy, reducing the complexity of manufacturing and corrosion resistance. The same profiles were also applied to other span elements – floor beams, roofs, and tie elements. Flat  two-member  supports  with  a  single-plane  diagonal  connecting  grid  were  designed.  Cross-sections  of  the  supports  are  designed  in  two  versions  –  with  the  hot  rolled  I-beams  №45  and alternatively from a composite light formed I-beam with a corrugated sinusoidal wall. The savings on all posts of conveyor gallery supports for the second version make 4.2 tons of steel.